Modulation instability and optical wave profiles for the conformable Schrödinger-Poisson dynamical system - Yasin, Muhammad Waqas; Baber, Muhammad Zafarullah; Munir, Muskan; Hassaballa, Abaker A.; İnç, Mustafa; Iqbal, Muhammad Sajid; Rezapour, Shahram (Springer, 2024)
This manuscript studies the exact solitary wave profiles for the conformable Schr & ouml;dinger-Poisson dynamical system. This system has a significant role in gravity's quantum state operation approximates the interaction between quantum mechanics and gravitation. The diverse exact solitary wave profiles are constructed by using the Khater method. The different closed-form solutions are obtained such as dark, singular, hyperbolic, periodic, and plane waves. Moreover, the modulation instability is also discussed for this dynamical system. To, show the physical significance of desired results we plot the 3D and 2D plots along with the related contour graphs, which are also drawn. The constraint criteria for the exact solutions are also exposed.
Keywords: Solitary waves; Schr & ouml;dinger-Poisson equation; Khater method; Stability analysis